Investigating the mode of action of intracellular loop 1 pepducins at the CXCR4 receptor - Caspar, Birgit (2019)
Background Pepducins are lipid-peptides derived from the intracellular loop sequences of a G protein-coupled receptor and have been shown to act as allosteric modulators. Pepducins have been described for the chemokine receptor, CXCR4, which can exhibit agonist activity in the absence of the endogenous ligand C-X-C-Ligand 12 (CXCL12). To date, their precise mode of action is unclear. In this study, we investigated the mechanism of action of intracellular loop 1 pepducins at the CXCR4 receptor Experimental Approach Experiments were performed in HEK293 cells stably expressing the GlosensorTM cAMP sensor (HEK293G) and human CXCR4 tagged with (a) NanoLuc on its N-terminus (NL-CXCR4), (b) C-terminus (CXCR4-NL), (c) SNAP on its N-terminus (SNAP-CXCR4), (d) human CCR5 or (e) human CXCR4 with the first internal loop swapped for the CCR5 sequence (CXCR4_CCR5il1). The binding of fluorescently labelled CXCR4 ligands and their displacement was quantified with a NanoBRET assay using NL-CXCR4 or CXCR4-NL cells. Conformational changes caused by CXCL12 and pepducins were monitored with an intramolecular biosensor and a BRET assay looking at dimerisation. Moreover, cells were tested in functional assays looking at G protein activation, cAMP inhibition, ß-arrestin recruitment and internalisation after the addition of endogenous ligand CXCL12 or pepducin. Results The affinity of fluorescent CXCL12 (CXCL12-red) was determined through NanoBRET saturation binding. Competition binding experiments showed that CXCL12-red binding was inhibited by addition of small molecules or ATI-2341. Control pepducins with no lipid tail or modified sequences were unable to displace CXCL12-red at concentrations up to 10 µM. ATI-2341f, a fluorescent version of ATI-2341, with an additional TAMRA tagged lysine on the N-terminal end of the sequence showed a displaceable increase in BRET ratio in CXCR4-NL, but only a small change in NL-CXCR4 membranes. An intramolecular biosensor showed activation of CXCR4 by CXCL12 and ATI-2341. However, activation by ATI-2341 was delayed by 30 s. Dimers measured via BRET from one receptor to another showed an increase in BRET with CXCL12 and a decrease in BRET with ATI-2341. Functional assays showed similar activation of CXCR4 by CXCL12 and ATI-2341. An ATI-2341 threonine to alanine mutant showed reduced potencies in all tested assays. Key Conclusion These data suggest that ATI-2341 follows the previously proposed interaction mechanism of pepducins. In a first step, the lipid tail interacts with the membrane and the pepducin is flipped into the cell as supported by the 30 s activation delay observed with ATI-2341 in comparison to the endogenous ligand. Then, the interaction of ATI-2341 and CXCR4 takes place at the intracellular part of the receptor as suggested by the BRET binding studies. However, this interaction impacts the endogenous binding pocket of CXCL12. Furthermore, the functional activation of CXCR4 by CXCL12 is similar to the one observed with ATI-2341. The only difference can be observed in dimerisation and ß-arrestin recruitment experiments. Mutations of the pepducin identified the threonine as an important amino acid.